A Digest of the Acts of Assembly Relating to and the General Ordinances of the City of Pittsburgh, from 1804 to Jan. 1, 1897, Ordinances-Executive Departments, Bureau of Parks (1893) - (:unkn) unknown (My University, 1893)
Prohibited carry of firearms, shooting or throwing of stones, or setting snares within the limits of the park or within one hundred yards thereof.
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE